Adsorption of Fluoride Ion on Activated Carbon Prepared from Delonix regia Dry Fruits - Kishore, Medikondu; Surendra Babu*, K.; Krishna Murthy, M. (Asian Journal of Chemistry, 2014)
In this article, activated carbon prepared from Delonix regia dry fruits and applied to remove excessive fluoride from aqueous solution. The adsorption mechanism of F– ions from aqueous media onto the surface of activated carbon with the help of different advanced technologies like X-ray diffraction, SEM-EDX, FT-IR and thermogravimetric analysis is studied. The chemistry of adsorbent surface was characterized by applying X-ray photoelectron spectroscopy.